A study on factors that influences public participation in local government activities: a case study of Majlis Bandaraya Melaka Bersejarah (MBMB) / Noor Aleena Izmim Azhar and Rohaizatul Shima Nik - Azhar, Noor Aleena Izmim; Nik, Rohaizatul Shima (Faculty of Administrative Science and Policy Studies, 2014)
This study has been carried out to identify the factors that influence public participation in local government activities in Majlis Bandaraya Melaka Bersejarah (MBMB) by specifically focused on the residents in the area of jurisdiction. A sample size of 351 residents was involved in this study. The main objective of this study is to identify the mostly affected factors that influence public participation in local government (MBMB) activities whether it influenced by awareness, experiences and social exclusion. The statistic techniques used in this study are Descriptive Statistics, Regression analysis, and Spearman’s rank-order correlation analysis. This study revealed that the most affected factor that influence public participation is public’s experiences. Moreover, there is moderate relationship under public’s awareness and social exclusion. This study also provides significant information and recommendation as a future references to other research.